Effects of pulse length on low frequency plasma nitrided 316L steels. (August 2015) - Díaz-Guillén, J. C.; Vargas-Gutiérrez, G.; Granda-Gutiérrez, E. E.; González, M. A.; Díaz-Guillén, J. A.; Alvarez-Contreras, L.
Abstract : The influence of pulse time ( t p ) variation on hardness, crystalline phases and electrochemical corrosion susceptibility of plasma nitriding 316L was investigated. Hardness test, X-ray diffraction, scanning electron microscopy and electrochemical polarisation tests let to identify the best processing conditions. Nitriding at t p = 5 ms in a 100 Hz discharge increased the 316L hardness around four times and decreased its corrosion susceptibility one order of magnitude. The X-ray diffraction analysis showed the shifted reflections for the expanded austenite and let to identify an anisotropic strain with expansion lattice around 7·5 and 9% for (111) and (200) orientations respectively. For the evaluated t p range, the increase in the pulse length has not beneficial influence on surface hardness; on the contrary, there is a decrease in its value when t p grew from 5 to 8 ms. Corrosion and hardness performance has been related to the strain level and to the nitrogen content.